Reviewing Grasha Teaching Methods among Faculty Members of Shiraz Medical School - Mitra Amini; Sahar Samani; Farhad Lotfi (Tabriz University of Medical Sciences, 2012)
Introduction: Teaching and training are the basic responsibly of a faculty member. One of the fundamental problems of education in the universities is not having a criterion to identify the effective teaching styles. The aim of this study was to determine Grasha teaching method among the faculty Members in Shiraz Medical School. Methods: this descriptive, cross- sectional study was done on 100 faculty members who were selected by census sampling method. Data collection method was Grasha questionnaire which contains 40 questions in 5 sections. Data were analyzed by SPSS 18. Results: All questionnaires were completed. The age range was from 32 to 65 and the mean age was 46. 57% were male. There were 27 PhD, 35 specialists and 38 subspecialists. The highest average score belonged to "Expert" method (2/66±0/55) and the lowest to "Personal" (2± 0/76). 96% of the academic staffs were inclined to "Expert" method and %97, %83, %78, %80 to "Formal", "Personal", "Delegator" and "Facilitating" methods, respectively. There was no significant difference between male and female, but in "Expert" method, the average of females was superior. %77 was under 50 years and %23 over 50. There was no significant difference between elder and younger academic members. No significant difference was found in terms of university degree. Conclusion: This study suggested academic members are inclined to use "Expert" and Delegator methods. Therefore, it is necessary for the academic members to choose a method which creates intellectual excitement among the students through the clarity of teaching content and understanding among individuals that increase the efficiency of their methods.